How does Moko disease or bacterial wither of banana plants? / Mariam Setapa and Siti Maziah Ab Rahman - Setapa, Mariam; Ab Rahman, Siti Maziah (UiTM Cawangan Negeri Sembilan, 2023)
Currently, bacterial wilt disease, of the known as Moko disease, has infected the majority of banana trees. Farmers and businesses that handle bananas suffered significant losses as a result of the disease since they were unable to sell the banana-related goods. Bananas affected by this plant will be completely damaged. Banana Moko Disease or better known as Banana Plant Bacterial Wilt Disease is a disease caused by Ralstonia solanacearum bacterial infection. This bacterium is found in the soil and it can live on the host for 2 to 3 years. R. solanacearum is a gram negative bacterium and it grows aerobically (requires air) and does not produce spores. According to Stevenson (2001), bacterial growth in Broth culture can be inhibited by salt solution (NaCl) with a concentration of more than 2%. This bacterium does not only attack banana trees, but it also attacks other trees such as tomatoes, potatoes, eggplant and tobacco. These bacteria are usually found in tropical, subtropical and some temperate regions of the world.